2016
DOI: 10.1097/icu.0000000000000273
|View full text |Cite
|
Sign up to set email alerts
|

Use of adjunctive topical corticosteroids in bacterial keratitis

Abstract: Purpose of review Topical corticosteroid use in the setting of infectious keratitis has been a controversial issue. The aim of this review is to provide an update on the evidence for use of topical corticosteroids in addition to antibiotics in bacterial keratitis. Recent findings Judicious use of steroids is postulated to limit the inflammatory component of bacterial keratitis, but can theoretically retard healing. Three small randomized controlled trials and one large-scale trial, the Steroids for Corneal U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…The role of corticosteroids in the treatment of infectious scleritis remains controversial. 32 There can be a robust inflammatory response after microbial invasion of the eye wall, which itself can cause significant damage 33, 34 However, the timing, dosage, and delivery of corticosteroids in scleritis is not yet known. Our study is encouraging; as similar to the SCUT trial, we found no adverse effects of oral corticosteroids in our population.…”
Section: Discussionmentioning
confidence: 99%
“…The role of corticosteroids in the treatment of infectious scleritis remains controversial. 32 There can be a robust inflammatory response after microbial invasion of the eye wall, which itself can cause significant damage 33, 34 However, the timing, dosage, and delivery of corticosteroids in scleritis is not yet known. Our study is encouraging; as similar to the SCUT trial, we found no adverse effects of oral corticosteroids in our population.…”
Section: Discussionmentioning
confidence: 99%
“…No significant benefit nor worsening effects were seen with corticosteroids. However, another sub-group analysis of SCUT focusing on cytotoxic (ExoU) vs invasive (ExoS) subtypes of P. aeruginosa revealed that adjunctive corticosteroid therapy initiated at 48 h after antibiotic treatment is beneficial for resolution of keratitis caused by invasive strains [68, 69]. …”
Section: Corticosteroidsmentioning
confidence: 99%
“…In addition, the use of steroid eyedrops during hospitalization and the treatment for bacterial keratitis remains controversial, as this may lead to progression of corneal thinning or damage. [9] Two weeks after the initiation of treatment with 1% prednisone acetate eyedrops in the present case, marked thinning of the area in which Pseudomonas keratitis had developed was confirmed using anterior segment optical coherence tomography, although the infiltrates at the corneolimbal junction had not yet completely resolved.…”
Section: Discussionmentioning
confidence: 54%